Essential Oil Constituents and Antifungal Activity of Plectranthus japonicus K. - Mathpal, Disha; Mathpal, Rajesh; Shah, G.C.; Gupta, R.C. (Asian Journal of Chemistry, 2010)
The chemical constituents of the essential oil from Plectranthus japonicus K. have been identified by using GC, GC-MS and spectral analysis. The oil was screened for antifungal activity against Aspergillus niger, Alternaria alternata, Penicillium citrimum, Rhizopus nigricans and Trichodermis viride.